Intersection of Inflammation and Senescence in the Aging Lung Stem Cell Niche - Allen, Nancy C.; Reyes, Nabora S.; Lee, Jin Young; Peng, Tien (Frontiers in Cell and Developmental Biology, 2022)
Aging is the final stage of development with stereotyped changes in tissue morphology. These age-related changes are risk factors for a multitude of chronic lung diseases, transcending the diverse pathogenic mechanisms that have been studied in disease-specific contexts. Two of the hallmarks of aging include inflammation and cellular senescence that have been attributed as drivers of age-related organ decline. While these two age-related processes are often studied independently in the same tissue, there appears to be a reciprocal relationship between inflammation and senescence that remodels the aging tissue architecture to increase susceptibility to chronic diseases. This review will attempt to address the “chicken or the egg” question as to whether senescence drives inflammation in the aging lung, or vice versa, and whether the causality of this relationship has therapeutic implications for age-related lung diseases.